The Effects Of Structure-Based Production Tasks On English Non-Majored Students’ Attitudes And Grammatical Performance - Nguyễn, Thy Quỳnh; Nguyễn, Hương Thu (Advances in Social Sciences Research Journal, 2017)
The main purpose of the current study was to investigate the effectiveness of the Structure-Based Production Tasks on English non-majored students’ attitudes and grammatical performance. Fifty nine students of Ton Duc Thang University were conveniently selected and assigned into two groups: experimental group and control group. The experimental group was introduced with the alternative approach [Task-based approach] while the control group learned with the traditional approach [Presentation-Practice-Production]. The collected data was analyzed to find out the differences between two groups in terms of the Discrete-point item test and the Integrative item test. A questionnaire-based survey was also employed to explore students’ attitudes towards the treatment. The statistic result revealed that the experimental group did not exceed the control group although its result was slightly higher than that of the other. However, the significant difference of the experimental learners in the Integrative item post-test indicated that the Structure-Based Production Tasks were effective in grammar teaching. In addition, the experimental group had favorable attitudes towards the treatment. Briefly, the results of the study have offered foundations for intriguing implications withdrawn from the study to improve grammar teaching.